European universities from the Enlightenment to 1914 - Anderson, R. D. (Robert David) (Oxford University Press, 2004)
An essential contribution both to modern European history, and to understanding the background of contemporary university problems, Robert Anderson provides an authoritative account of the development of European universities in the 'long' 19th century.